Treatment of a Prolonged Air Leak with Radiotherapy: A Case Report - Erdoğan Çetinkaya; M. Akif Özgül; Şule Gül; Ertan Çam; Yakup Büyükpolat (Case Reports in Pulmonology)
Pneumothorax is defined as air in the pleural space. Depending on the severity of the pneumothorax, treatment consists of oxygen therapy, simple aspiration, tube thoracostomy, and pleurodesis. Prolonged air leakage is observed in 25% of the patients who have undergone surgical procedures, such as thoracotomy, pleurectomy, and video-assisted thoracoscopy. The patient presented here is the third reported case successfully treated with radiotherapy. Ventilation scintigraphy was used to localise the air leak, and localised radiotherapy was performed at the targeted location. After radiotherapy, the air leak ceased and at the 3-month followup, the pneumothorax had not recurred. Radiotherapy can be a treatment modality for patients with prolonged air leak, who are not candidates for surgery.